Disrupted Intraregional Brain Activity and Functional Connectivity in Unilateral Acute Tinnitus Patients With Hearing Loss - Zhou, Gang-Ping; Shi, Xin-Yi; Wei, Heng-Le; Qu, Li-Jie; Yu, Yu-Sheng; Zhou, Qing-Qing; Yin, Xindao; Zhang, Hong; Tao, Yue-Jin (Frontiers in Neuroscience, 2019)
Purpose: The present study combined fractional amplitude of low-frequency fluctuations (fALFF), regional homogeneity (ReHo) and functional connectivity (FC) to explore brain functional abnormalities in acute tinnitus patients (AT) with hearing loss. Methods: We recruited twenty-eight AT patients and 31 healthy controls (HCs) and ran resting-state functional magnetic resonance imaging (fMRI) scans. fALFF, ReHo, and FC were conducted and compared between AT patients and HCs. After that, we calculated correlation analyses among abnormal fALFF, ReHo, FC and clinical data in AT patients. Results: Compared with HCs, acute tinnitus patients showed increased fALFF values in the right inferior temporal gyrus (ITG). In contrast, significantly decreased ReHo values were observed in the cerebellar vermis, the right calcarine cortex, the right precuneus, the right supramarginal gyrus (SMG) and the right middle frontal gyrus (MFG). Based on the differences in the fALFF and ReHo maps, the latter of which we defined as region-of-interest (ROI) for FC analysis, the right ITG exhibited increased connectivity with the right precentral gyrus. In addition, the right MFG demonstrated decreased connectivity with both the bilateral anterior cingulate cortex (ACC) and the left precentral gyrus. Conclusions: By combining ReHo, fALFF, and FC analyses, our work indicated that acute tinnitus patients with hearing loss had abnormal intraregional neural activity and disrupted connectivity in several brain regions which mainly involving the non-auditory area, and these regions are major components of default mode network(DMN), attention network, visual network and executive control network. These findings will help us enhance the understanding of the neuroimaging mechanism in tinnitus populations. Moreover, these abnormalities remind us that we should focus on the early stages of this hearing disease.